National nitrogen budget for Germany. (16th September 2021) - Häußermann, Uwe; Bach, Martin; Fuchs, Stephan; Geupel, Markus; Heldstab, Jürg; Klement, Laura; Knoll, Lukas; Reutimann, Judith; Schäppi, Bettina; Weber, Tatyana; Breuer, Lutz
Abstract: Emissions of reactive nitrogen (Nr ) give rise to a wide range of environmental problems. Nitrogen budgets for various systems and on different scales are an established tool to quantify the sources and fate of Nr . The national nitrogen budget (NNB) for Germany calculates the nitrogen flows for eight pools: Atmosphere, Energy and Fuels, Material and Products in Industry, Humans and Settlements, Agriculture, Forest and Semi-natural Vegetation, Waste, and Hydrosphere, as well as for the transboundary N-flows. In Germany, in total 6, 275 kt Nr a −1 has been introduced into the nitrogen cycle annually (mean 2010 to 2014), of which 43% stem from ammonia synthesis. Domestic extraction and import of nitrogenous fossil fuels (lignite, coal, crude oil) releases another 2, 335 kt Nr a −1 . Import of food, feed and materials contributes 745 kt Nr a −1, while biological N fixation converts 308 kt Nr a −1 into organically bound nitrogen. In terms of Nr sinks, the combustion and denoxing of fuels and the refining of crude oil converts 2, 594 kt Nr a −1 to N2 . In waters, soils, and wastewater treatment plants, denitrification leads to the release of 1, 107 kt Nr a −1 as N2 . Via the atmosphere and hydrosphere, Germany exports 755 kt Nr a −1 to neighbouring countries and into coastal waters. On balance, Germany releases 1, 627 kt Nr a −1 annually to the environment. However, the NNB as a whole and the individual pool balances involve substantial uncertainties, which have to be considered when interpreting the results.